Analyzing Architecture of Mithraism Rock Temples - AliJabbari, Zohre (Journal of History Culture and Art Research, 2017)
This analyzes the architecture of rock temples of West and Northwest of Iran, as well as factors influencing their formation. The creation of rock architecture in this area of Iran is influenced by the religious, geographical and political atmosphere of their time. Most of these structures are formed by dominated empires in the first millennium BC. And in some works we are observing their continuity in later periods and change in their functions. One of the reasons that have attracted man to mountain and rock in different schools was the religious structure of community. According to the sanctity of mountains and rocks in the ancient religions, especially in Mithraism, valuable temples and places of worship have emerged in the mountains. Their obvious characteristic is circular dome-shaped spaces; simplicity, arrangement of spaces and the way of creating light that correspond with the tradition of Mithraism in Iran. Mehr Temple in Maragheh, Dashkasan in Zanjan, and Qadamgah Temple in Azarshahr are the rock temples in northwest of Iran that signs and symbols on them indicate the performance of Mithraism duties in these temples. In the West of Iran, Cogan cave in Lorestan, considering the characteristics of Mithraism temples, in a period had function as a temple for the worship of Mithra. This research investigates architectural futures of these temples.